Sustainable HRM: Integrating Green Human Resource Management Practices for Organizational Resilience - Munziar, Fakhri; Hodijah, Cucu (Journal of Economics and Management Scienties, 2025)
This paper explores the strategic role of Green Human Resource Management (Green HRM) in enhancing organizational resilience within the broader paradigm of Sustainable HRM. Drawing from theoretical frameworks such as the Resource-Based View, Dynamic Capabilities, and Stakeholder Theory, the study develops a model linking five Green HRM practices—green recruitment, green training, green performance management, green rewards, and green employee involvement—to five distinct resilience capabilities: adaptive capacity, human capital agility, organizational robustness, innovation readiness, and collective resilience. The framework posits that these HRM practices, when embedded strategically and supported by sustainability-oriented leadership and learning cultures, contribute not only to environmental outcomes but also to the organization’s ability to withstand and adapt to environmental, regulatory, and operational disruptions. Practical examples from companies such as Patagonia, Unilever, and Infosys are used to illustrate real-world applications of the framework. The study concludes that Green HRM is a critical yet underutilized enabler of long-term organizational resilience and offers actionable recommendations for aligning HRM systems with sustainability goals. This work contributes to both the theoretical development and practical advancement of Sustainable HRM as a driver of strategic adaptability in the face of ecological complexity.